1986
DOI: 10.3382/ps.0651225
|View full text |Cite
|
Sign up to set email alerts
|

Fat Deposition in a Broiler Sire Strain I. Phenotypic and Genetic Variation in, and Correlations Between, Abdominal Fat, Body Weight, and Feed Conversion

Abstract: Variability in body composition was examined weekly from 3 to 10 weeks of age in chickens from a broiler sire strain. Genetic aspects of body weight, quantity of abdominal fat, and feed conversion were examined in pedigree birds of the same strain at 6 weeks of age.Variability in abdominal fat relative to body weight (RAF), total percentage of carcass fat, and body weight (BW) was not influenced by sex or age. The phenotypic correlation (rp) between RAF and BW was generally positive, but low (between .20 and .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
16

Year Published

1987
1987
2000
2000

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 12 publications
4
17
0
16
Order By: Relevance
“…Eitan et al (1982) and Leenstra et al (1986) found negative genetic correlations between body weight gain with restricted feeding and amount of abdominal fat deposited with ad libitum feeding. Eitan et al 1982) used individual housing, while Leenstra et al (1986) housed the chickens in groups. Selection for body weight among grouphoused chickens, which are fed restricted, can be applied easily to large numbers of chickens.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Eitan et al (1982) and Leenstra et al (1986) found negative genetic correlations between body weight gain with restricted feeding and amount of abdominal fat deposited with ad libitum feeding. Eitan et al 1982) used individual housing, while Leenstra et al (1986) housed the chickens in groups. Selection for body weight among grouphoused chickens, which are fed restricted, can be applied easily to large numbers of chickens.…”
Section: Introductionmentioning
confidence: 95%
“…However, measurement of both characteristics is laborious and individual selection for feed conversion requires individual cages (Pym and James, 1979). Eitan et al (1982) and Leenstra et al (1986) found negative genetic correlations between body weight gain with restricted feeding and amount of abdominal fat deposited with ad libitum feeding. Eitan et al 1982) used individual housing, while Leenstra et al (1986) housed the chickens in groups.…”
Section: Introductionmentioning
confidence: 98%
“…In broiler chickens, the correlation coefficient between live body weight and abdominal fat weight was 0.50 [26], and 0.49 and 0.53 for males and females, respectively [4]. Also, Leenstra et al [12] estimated the correlation between live body weight and abdominal fat weight as 0.46. Weight of carcass and non-carcass components were positively intercorrelated.…”
Section: Their Relationship With Each Other and With Live Body Weightmentioning
confidence: 99%
“…In a literature review by Leenstra [11] the coefficient of variation of the abdominal fat weight of broiler reared in the same environment varied from 24 to 47%. The large variability of this trait along with its high heritability offers favourable prospects for selection against this trait [12]. of the original 5 variables, leaving 27.1% to the 5 'special' factors (Tab.…”
Section: Varimax Rotated 'Independent' Factors Their Interpretationmentioning
confidence: 99%
“…These two traits are commonly used in determining performance of both meat and egg-type birds. Further, these traits with an estimated correlation of +0.52 have been of both biological and economic significance towards genetic improvement through selection of faster growing and high producing birds (Chambers et al, 1984;Leenstra et al, 1986).…”
Section: Introductionmentioning
confidence: 99%